Judging the Climate: Comparative Human Rights Approaches to Climate Litigation in Global Courts - Hermansyah (Indonesian Scientific Publication, 2025)
Climate change increasingly threatens fundamental human rights, prompting courts worldwide to intervene where legislative and executive actions fall short. This article examines how climate litigation enforces human rights obligations through judicial mechanisms, focusing on landmark rulings in Switzerland, India, and the United States. Using a mixed-methods approach that combines comparative doctrinal analysis and an empirical panel dataset (2015–2025), the study tracks litigation frequency, rights-based victories, and climate law intensity across jurisdictions. Findings show that courts are progressively recognizing climate-related rights and issuing binding decisions mandating state action. In KlimaSeniorinnen v. Switzerland, the ECtHR found that weak climate policy violated the right to private life; India’s Supreme Court affirmed environmental protection as a constitutional right in Ranjitsinh; and the Montana Supreme Court upheld youth rights in Held v. Montana. The data indicate a positive correlation between strong legal frameworks and successful litigation, leading to policy reforms and cross-border influence in legal reasoning. Despite significant progress, enforcement remains constrained by political resistance and limited administrative capacity. Civil society continues to play a vital role in promoting accountability and bridging implementation gaps. Overall, rights-based climate litigation is transforming climate governance by embedding human rights principles within environmental adjudication, signaling an emerging global legal consciousness that strengthens both environmental protection and justice.